2021
DOI: 10.1007/s00787-021-01804-8
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Response Treatment with and without robot-assistance for children with autism: a randomized controlled trial

Abstract: Pivotal response treatment (PRT) is a promising intervention focused on improving social communication skills in children with autism spectrum disorder (ASD). Since robots potentially appeal to children with ASD and may contribute to their motivation for social interaction, this exploratory randomized controlled trial (RCT) was conducted comparing PRT (PRT and robot-assisted PRT) with treatment-as-usual (TAU). Seventy-three children (PRT: n = 25; PRT + robot: n = 25; TAU: n = 23) with ASD, aged 3–8 years were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
(66 reference statements)
1
16
0
1
Order By: Relevance
“…social-communication skills) but also collateral gains on the development of the child, this study included measures on widespread child and parent outcomes. The results on the independent clinician rated CGI indicated less severe clinical symptoms in global functioning at the end of the intervention, which is in line with previous findings 15 , 21 , 45 , 46 . Also, the improvement rating of the CGI (CGI-I) demonstrated that 80% of the participants showed improvement in global functioning, of which 22% of the participants represented a substantial change and could be indicated as a clinical responder ( very much improved or much improved ).…”
Section: Discussionsupporting
confidence: 91%
“…social-communication skills) but also collateral gains on the development of the child, this study included measures on widespread child and parent outcomes. The results on the independent clinician rated CGI indicated less severe clinical symptoms in global functioning at the end of the intervention, which is in line with previous findings 15 , 21 , 45 , 46 . Also, the improvement rating of the CGI (CGI-I) demonstrated that 80% of the participants showed improvement in global functioning, of which 22% of the participants represented a substantial change and could be indicated as a clinical responder ( very much improved or much improved ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the scenario, if we analyze the duration of the interventions carried out, we see that more than half of them have lasted less than a month. Related to everything mentioned above, as many author affirm (Van der Berk-Smeekens, de Korte, van Dongen-Boomsma, Oosterling, den Boer, Barakova & Buitelaar, 2021;Chung, 2021)routines are essential for people on the autism spectrum, so an educational intervention must be adapted to their school schedule and become a routine. This goal cannot be achieved in less than a month.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that children performing with the RAT significantly improved their socio-emotional skills with respect to the control group. Van den Berk-Smeekens et al [ 13 ] conducted a randomized controlled trial using Pivotal Response Treatment (PRT) with and without NAO robot assistance for improving the social skills of children with ASD. Seventy-three children were randomly assigned into three groups (PRT: n = 25; PRT + robot: n = 25; standard intervention: n = 23).…”
Section: Social Humanoid Commercial Robotsmentioning
confidence: 99%